Does Indonesia Need Corporate Farms? Reflections on Modernization, Efficiency, and The Social Function of Land - White, Ben (Journal of Rural Indonesia [JORI], 2013)
Indonesia faces serious problems in agricultural development and its relation to food security, employment, and sustainability. Today, Indonesia is importer country of rice and other commodities that can actually flourish in Indonesia. Meanwhile, currently Indonesia is becoming the world’s biggest producer and exporter of palm-oil. Ironically, Indonesia has converted the most fertile agricultural land to other uses, and cut down its timber for the sake of planting oil palm. Indonesia also faces unemployment problem. Agricultural sector is unattractive to young people. Agricultural sector should keep growing to be able to assure food security and absorb labor force. However, there is no guarantee that modern, efficient, and innovative agriculture requires large scale farming (corporate farming). © 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: agricultural development, corporate farming, food security